The Differences of Block Exam Scores Based on Students Organization Activities in Faculty of Medicine Sebelas Maret University - Aulia Muhammad Fikri; Sinu Andhi Jusup; Amandha Boy Timor Randita (Nexus Pendidikan Kedokteran dan Kesehatan, 2015)
Background: Hard skills and soft skills are important abilities for student to be learned. Hard skills can be acquired through lectures activities while the soft skills and spiritual can be acquired through extracurricular activities, so student needs to join extracurricular activities in addition to lectures activities. However, a lot of people think that active in organization can affect academic achievment. Lack of time due to organization activities can affect academic achievment.This study aimed to analyze the difference of block exam scores based on students organization activities in Faculty of Medicine Sebelas Maret University. Method: This study was an observational analytic study with cross sectional approach. One hundred and fifty students of Faculty of Medicine Sebelas Maret University class of 2012 were randomly drawn by simple random sampling technique. The organizational activity questionnaire consist of 20 question with multiple choice answer options. Block exam scores were obtained from medical faculty. The data were analyzed with Independent T-Test. Result: Ninety eight student were active in organizations and52studentswere notactive in organizations. Average score of student who were active at organization was 62,44. While average score of student who were not active at organization was 63,85.The result of Independent T-Test was p= 0.240 (p> 0.05). Conclusion: There was no difference in block exam scores between student who were active and not active in organization in Faculty of Medicine Sebelas Maret University. Keywords: organization activities, block exam score